The natural course of microalbuminuria among African American with type 2 diabetes: A 3 year study - Atta, Mohamed G (2009)
BACKGROUND: The natural course of microalbuminuria in African Americans (AA) with type 2 diabetes is not well established. METHOD: Longitudinal analysis of 186 AA with type 2 diabetes enrolled in Project Sugar, a randomized controlled trial of primary care-based interventions to improve diabetes control. RESULTS: Mean age was 59.4 and 85% were female. Mean estimated glomerular filtration rate (eGFR) and urinary albumin-to-creatinine ratio (ACR) were 75.90 ml/min/1.73 m(2) and 1.62 respectively. Thirty nine patients had macroalbuminuria and significantly higher systolic blood pressure compared to those with microalbuminuria (p=0.01). Sixty patients had microalbuminuria, 19 progressed to macroalbuminuria and none regressed. Progression was significantly associated with systolic blood pressure ≥ 115 and requirement for blood pressure medication in the univariate model. In the multivariate model, the degree of ACR (odds ratio [OR] = 35.51, 95% CI 2.21, 571.65) and need for blood pressure medication (OR= 8.96, 95% CI 1.35, 59.70) were independently associated with progression. No association observed with the use of specific antihypertensive agent. CONCLUSION: This study suggests that AA with type 2 diabetes and microalbuminuria experience irreversible disease that not infrequently progresses to overt proteinuria. The degree of microalbuminuria and blood pressure are key determinants in this process and should be primary targets in treating this population regardless of the antihypertensive class used.